The Nursing Home Physical Performance Test: A Secondary Data Analysis of Women in Long-Term Care Using Item Response Theory. (11th April 2017) - Perera, Subashan; Nace, David A; Resnick, Neil M; Greenspan, Susan L
Abstract: Background and Objectives: The Nursing Home Physical Performance Test (NHPPT) was developed to measure function among nursing home residents using sit-to-stand, scooping applesauce, face washing, dialing phone, putting on sweater, and ambulating tasks. Using item response theory, we explore its measurement characteristics at item level and opportunities for improvements. Research Design and Methods: We used data from long-term care women. We fitted a graded response model, estimated parameters, and constructed probability and information curves. We identified items to be targeted toward lower and higher functioning persons to increase the range of abilities to which the instrument is applicable. We revised the scoring by making sit-to-stand and sweater items harder and dialing phone easier. We examined changes to concurrent validity with activities of daily living (ADL), frailty, and cognitive function. Results: Participants were 86 years old, had more than three comorbidities, and a NHPPT of 19.4. All items had high discrimination and were targeted toward the lower middle range of performance continuum. After revision, sit-to-stand and sweater items demonstrated greater discrimination among the higher functioning and/or greater spread of thresholds for response categories. The overall test showed discrimination over a wider range of individuals. Concurrent validity correlation improved from 0.60 to 0.68 for instrumental ADL and explained variability ( R 2 ) from 22% to 36% for frailty. Discussion and Implications: NHPPT has good measurement characteristics at the item level. NHPPT can be improved, implemented in computerized adaptive testing, and combined with self-report for greater utility, but a definitive study is needed.